CSI501 - Computer Organisation August/September 1998 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1998)
UNIVERSITI SAINS MALAYSIA First Semester Examination Academic Session 1998/99 August/September 1998 CSI501 - Computer Organisation